Perbandingan Kepadatan dan Keanekaragaman Diatom (Bacillariophyceae) pada Thallus Kappaphycus alvarenzii dan Eucheuma denticulatum pada Kedalaman Berbeda di Perairan Desa Tanjung Tiram Kecamatan Moramo Utara Kabupaten Konawe Selatan - Ulfa, Hartina; Kasim, Ma`ruf; Irawati, Nur (Jurnal Manajemen Sumber Daya Perairan, 2020)
Diatoms or bacillariophycea are very important as contributors to primary productivity in both pelagic and benthic waters. This study aims to determine the ratio of density and diversity of diatoms (Bacillariophyceae) on the thallus K. alvarezii and E. denticulatum at different depths. This research was carried out in the waters of Tanjung Tiram Village, North Moramo District, Konawe Selatan District. Water quality analysis and sample identification were conducted at the UHO FPIK Testing Laboratory, research was conducted in June to August 2019. Sampling is done randomly on the third inside. Sampling at each depth of 6 thallus is divided into 2 types of marine assemblage 3 of E. denticulatum and 3 of K. alvarezii so the total sample at the 10th day of observation was 18 thallus. This also applies to sampling the 20th and 30th day. The result of diatom density from seaweed K. alvarezii and E. denticulatum obtained diatom density between K. alvarezii seaweed 50 cm depth 454535 Cell / cm2 Depth 100 cm that is 118918 Cell / cm2 and depth 200 cm that is 74357 Cell / cm2 sea E. denticulatum depth of 50 cm is 17876 cells / cm2, depth of 100 cm is 58109 cells / cm2 and and depth of 200 cm is 47237 cells / cm2. Diversity value in seaweed K. alvarezii Depth of 50 cm is 0.136 Cell / cm2, depth of 100 cm is 0.168 Cell / cm2, and depth of 200 cm is 0.167 Cell / cm2, while seaweed E. denticulatum depth of 50 cm is 0.152 Cell / cm2, a depth of 100 cm is 0.124 cells / cm2, and a depth of 200 cm is 0.151 cells / cm2, there is no high diversity this is because the number of species found is still very small so the value of diversity is also low.Keywords: Density, Diatoms, Diversity, Waters of Tanjung Tiram, Verty Net